Development CPS Integrated TPACK Model to Improve Student Problem Solving In New Normal Pandemic Covid-19 - Waluyo, Edy; Nuraini, Nuraini (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
In 21st-century learning, teachers must integrate technology, pedagogy knowledge, and content to improve students' problem-solving skills. Through problem-solving, students are required to think systematically, critically, logically, and have an unyielding attitude to find solutions to problems. This study aims to develop CPS integrated TPACK model to improve problem-solving capabilities. Borg and Gall model development research uses the research method, including needs analysis, product design, product development, product implementation, and evaluation. Data analysis was used in this study using descriptive analysis. Based on the data analysis conducted, the average product validation score of 3 experts in a row was 79.4; 79,9; and 80.8 in the valid category. The products developed are also relatively practical, with an average practical score of 82.67. The product trials were conducted four times the meeting showed that the products used are classified as pragmatic. The product is classified as effective with an effectiveness percentage of 86.67%, so it is feasible to be implemented. The product developed has a potential effect in the high category to improve math problem-solving skills with an N-Gain of 0.81.